Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper focuses on the selected issues of the Indonesian economy: (1) banking sector condition in India, (2) corporate vulnerabilities, (3) analysis of macrofinancial linkages in Indonesia, and (4) infrastructure development in Indonesia. Overall, the banking sector appears well capitalized and profitable. However, rising vulnerabilities from corporate foreign currency leverage and challenging financial market conditions have raised concerns. The risk from the corporate sector remains manageable, and the authorities have strengthened the monitoring framework. Macrofinancial linkages are analyzed using two complementary approaches: sector-level balance sheet analysis and a panel vector autoregressive approach. This paper addresses macrofiscal issues surrounding infrastructure development in Indonesia.